Case report: An intraretinal macrocyst with crystalline content and retinal detachment - Cai, Chang; Zhou, Jialin; Wang, Qiuyu; Li, Weihou; Liu, Danning (Frontiers in Medicine, 2022)
Introduction: An intraretinal macrocyst is a cavity located in the outer plexiform layer of the retina. It is commonly filled with liquid or blood. To date, few case reports of intraretinal macrocysts with crystalline content have been published. Case Presentation: A 44-year-old woman with no history of other diseases complained of decreased vision in her right eye that had persisted for 20 days. Comprehensive ophthalmic examinations were performed, including a vision test, slit lamp fundus examination, ocular B-scan ultrasound, and orbital magnetic resonance imaging. We performed vitrectomy and retinotomy to sufficiently remove the macrocyst and relieve retinal traction. During the surgery, we found that the cyst had crystalline content, which has not been previously reported, to the best of our knowledge. Finally, the pathological results confirmed a final diagnosis of intraretinal macrocyst. Six months later, we performed a second operation to remove the silicone oil and implant an intraocular lens. After both surgeries, the patient's vision improved. Conclusion: Intraretinal macrocysts are very rare. Both orbital magnetic resonance imaging and ocular B-scan ultrasound are essential for their diagnosis. Our results indicated that vitrectomy was the best way to remove the cyst and reattach the retina.